Pediatric Autoimmune Disorders Associated with Streptococcal Infections and Tourette's Syndrome in Preclinical Studies - Spinello, Chiara; Laviola, Giovanni; Macrì, Simone (Frontiers in Neuroscience, 2016)
Accumulating evidence suggests that Tourette’s Syndrome (TS) – a multifactorial pediatric disorder characterized by the recurrent exhibition of motor tics and/or vocal utterances – can partly depend on immune dysregulation provoked by early repeated streptococcal infections. The natural and adaptive antibody-mediated reaction to streptococcus (STREP) has been proposed to potentially turn into a pathological autoimmune response in vulnerable individuals. Specifically, in conditions of increased permeability of the blood brain barrier, STREP induced antibodies have been proposed to: (i) reach neuronal targets located in brain areas responsible for motion control; and (ii) contribute to the exhibition of symptoms. This theoretical framework is supported by indirect evidence indicating that a subset of TS patients exhibit elevated streptococcal antibody titers upon tic relapses. A systematic evaluation of this hypothesis entails preclinical studies providing a proof of concept of the aforementioned pathological sequelae. These studies shall rest upon individuals characterized by a vulnerable immune system, repeatedly exposed to streptococcus, and carefully screened for phenotypes isomorphic to the pathological signs of TS observed in patients. Preclinical animal models may thus constitute an informative, useful tool upon which conducting targeted, hypothesis-driven experiments. In the present review we discuss the available evidence in preclinical models in support of the link between TS and pediatric autoimmune neuropsychiatric disorders associated with streptococcus infections (PANDAS), and the existing gaps that future research shall bridge. Specifically, we report recent preclinical evidence indicating that the immune responses to repeated streptococcal immunizations relate to the occurrence of behavioral and neurological phenotypes reminiscent of TS. By the same token, we discuss the limitations of these studies: limited evidence of behavioral phenotypes isomorphic to tics and scarce knowledge about the immunological phenomena favoring the transition from natural adaptive immunity to pathological outcomes.